PERAN LEMBAGA ADAT DAYAK TAMAN DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DITINJAU DARI PERSPEKTIF HUKUM EKONOMI - NIM. A1011211241, RIZA PUSPITA (Jurnal Fatwa Hukum, 2025)
Abstract Indonesia, with its cultural and ethnic diversity, has many ethnic groups that are governed by customary law systems, including the Dayak Taman tribe in Sibau Hilir Village, Kapuas Hulu Regency, West Kalimantan. The Dayak Taman community has customary institutions that not only preserve traditions but also function as economic legal instruments that support community welfare. This study aims to analyze the role of the Dayak Taman Customary Institution in improving community welfare from an economic law perspective. The method used is empirical legal research of a descriptive analytical nature. The data sources consist of primary data obtained through interviews with informants such as the Customary Chief, the Temanggung Chief, and the indigenous community, while secondary data includes relevant legal materials. The data was analyzed qualitatively to describe the role of the Dayak Taman Customary Institution in improving the welfare of the indigenous community. The Dayak Taman Customary Institution plays an important role in improving welfare through social economic law and development. In social economic law, customary institutions organize donations for bereaved families, carry out customary rituals, and support the economy through village fund management. In development economic law, the customary institution is involved in the maintenance of Rumah Betang. Regulatory support such as Village Law No. 6 of 2014 and Kapuas Hulu Regency Regulation No. 13 of 2018 strengthens the role of customary institutions in maintaining a balance between tradition, economy, and development. Keywords: Development Economic Law; Social Economic Law; Customary Institutions; Indigenous Peoples; Dayak Tribe Abstrak Indonesia, dengan keberagaman budaya dan suku bangsa, memiliki banyak kelompok etnik yang diatur melalui sistem hukum adat, termasuk Suku Dayak Taman di Desa Sibau Hilir, Kabupaten Kapuas Hulu, Kalimantan Barat. Masyarakat Dayak Taman memiliki lembaga adat yang tidak hanya menjaga tradisi, tetapi juga berfungsi sebagai instrumen hukum ekonomi yang mendukung kesejahteraan masyarakat. Penelitian ini bertujuan untuk menganalisis peran Lembaga Adat Dayak Taman dalam meningkatkan kesejahteraan masyarakat dari perspektif Hukum Ekonomi. Metode yang digunakan adalah penelitian yuridis empiris yang bersifat deskriptif analitis. Sumber data berupa data primer yang diperoleh melalui wawancara dengan narasumber seperti Kepala Adat, Kepala Temanggung, dan masyarakat adat, sementara data sekunder mencakup bahan hukum yang relevan. Data dianalisis secara kualitatif untuk menggambarkan peran Lembaga Adat Dayak Taman dalam meningkatkan kesejahteraan masyarakat adat. Lembaga Adat Dayak Taman berperan penting dalam meningkatkan kesejahteraan melalui hukum ekonomi sosial dan pembangunan. Dalam hukum ekonomi sosial, lembaga adat mengorganisir sumbangan untuk keluarga berduka, melaksanakan ritual adat, dan mendukung ekonomi melalui pengelolaan dana desa. Dalam hukum ekonomi pembangunan, lembaga adat terlibat dalam pemeliharaan Rumah Betang. Dukungan peraturan seperti UU Desa No. 6 Tahun 2014 dan Perda Kabupaten Kapuas Hulu No. 13 Tahun 2018 menguatkan peran lembaga adat dalam menjaga keseimbangan tradisi, ekonomi, dan pembangunan. Kata Kunci: Hukum Ekonomi Pembangunan; Hukum Ekonomi Sosial; Lembaga Adat; Masyarakat Adat; Suku Dayak